Enhanced Detection Probability of OD-Initiated SCC(Transgranular & Intergranular) in SS304 Tubes Using Array Eddy Current Testing - Subramanian Chandran; Larence Pushparaj; N Sankar; Nivash Sankar; Sebastien Savard; David Aubé; Jitender Yadav (e-Journal of Nondestructive Testing)
This study investigates the detection of stress corrosion cracking (SCC) using eddy current testing with bobbin and array probes. The conventional bobbin probe method has limitation in detecting some outer diameter (OD) initiated axial and circumferential cracks in SS304 tubes with a diameter of 25.4 mm and a thickness of 1.65 mm. In contrast, these cracks were detected by array probe technology at a higher probability of detection. This discrepancy led to a detailed examination of SCC detection in SS304 tubes by inducing Artificial SCC with varying depths.